Strategi Unggul Penguatan Kapasitas Logistik Perdagangan: Rencana Lima Tahun 2024-2029 - Vikaliana, Resista; Iskandar, Yelita Anggiane; Puspitasari, Eka; Febryan, Rio (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Increasingly fierce global economic competition requires countries to develop effective trade strategies. In 2023, Indonesia improved its competitiveness ranking from 44th to 34th place according to the IMD Global Competitiveness Index. However, this position is still below Malaysia (27th) and Thailand (30th). This research uses a mixed quantitative and qualitative approach to analyze competitiveness indicators such as technology, health, labor market, and financial system. SWOT analysis was used to identify strengths, weaknesses, opportunities and threats in Indonesia's trade strategy. Critical success factors (CSF) analysis was used to structure information needs in the management hierarchy. By considering the general and specific conditions of Indonesia's trade logistics, a trade policy and strategy can be formulated. The trade strategy obtained from SWOT and CSF analysis is: 1. Strengthening downstream trade policies, 2. Strengthening multi-sectorregulatory stakeholder cooperation, in integrated logistics and trade marketing policies, 3. Accelerating digitalization and developing a competitive logistics service ecosystem, 4. Reorganizing trade logistics systems and facilities and infrastructure.Therefore, accurate and strategic trade planning is essential to improve economic efficiency and effectiveness, as well as competitiveness in the global market.